Pengembangan Media Praktikum Virtual Analisis Logam Besi Secara Spektrofotometri UV-Vis Berbasis Microsoft Excel Sebagai Media Alternatif pada Praktikum Analisa Instrumen dan Pemisahan - Ibnu Khaldun*; M. Nasir; Zaskhia Maulida (Jurnal Pendidikan Sains Indonesia, 2022)
The outbreak of the Covid-19 virus (Corona virus disease-19) in Indonesia, precisely in early March 2020, the government issued a lockdown policy in several areas, self-isolation, physical distancing, and distance learning in education units. The face-to-face lecture system in the classroom is replaced with online or online learning, so that practicum activities are also carried out online. Undergoing virtual practicum, educators are required to be creative and innovative in choosing practicum media, this is needed to facilitate and motivate students in independent learning. One of the interactive learning media that can support online practicum is microsoft excel-based practicum media. This study aims to determine the feasibility of the media and student responses to the virtual practicum media analysis of ferrous metal spectrophotometrically based on microsoft excel. This study uses the research and development (RD) method with the ADDIE model. The research was conducted at the Department of Chemistry Education, Faculty of Teacher Training and Education, Syiah Kuala University (FKIP USK). The sample was selected by random sampling, obtained 23 students who took the Chemistry Practicum of Instrument Analysis and Separation courses. The research instrument used a media validation sheet, a student response questionnaire, and a system usability scale (SUS) questionnaire. Data analysis used the percentage formula. The results of the validation of the feasibility of the virtual practicum media analysis of ferrous metal spectrophotometry UV-Vis based on microsoft excel by experts obtained a percentage of 82% with a very feasible category. Students gave positive responses to the virtual practicum media for spectrophotometric analysis of ferrous metal based on microsoft excel, and the SUS questionnaire obtained a sufficient category